Precision Psychiatry Approach to Treat Depression and Anxiety Targeting the Stress Hormone System – V1b-antagonists as a Case in Point - Holsboer, Florian; Ising, Marcus (Pharmacopsychiatry, 2024)
The future of depression pharmacotherapy lies in a precision medicine approach that recognizes that depression is a disease where different causalities drive symptoms. That approach calls for a departure from current diagnostic categories, which are broad enough to allow adherence to the “one-size-fits-all” paradigm, which is complementary to the routine use of “broad-spectrum” mono-amine antidepressants. Similar to oncology, narrowing the overinclusive diagnostic window by implementing laboratory tests, which guide specifically targeted treatments, will be a major step forward in overcoming the present drug discovery crisis.A substantial subgroup of patients presents with signs and symptoms of hypothalamic-pituitary-adrenocortical (HPA) overactivity. Therefore, this stress hormone system was considered to offer worthwhile targets. Some promising results emerged, but in sum, the results achieved by targeting corticosteroid receptors were mixed.More specific are non-peptidergic drugs that block stress-responsive neuropeptides, corticotropin-releasing hormone (CRH), and arginine vasopressin (AVP) in the brain by antagonizing their cognate CRHR1-and V1b-receptors. If a patientʼs depressive symptomatology is driven by overactive V1b-signaling then a V1b-receptor antagonist should be first-line treatment. To identify the patient having this V1b-receptor overactivity, a neuroendocrine test, the so-called dex/CRH-test, was developed, which indicates central AVP release but is too complicated to be routinely used. Therefore, this test was transformed into a gene-based “near-patient” test that allows immediate identification if a depressed patient’s symptomatology is driven by overactive V1b-receptor signaling. We believe that this precision medicine approach will be the next major innovation in the pharmacotherapy of depression.
Keywords: depression; anxiety disorders; precision psychiatry; HPA axis; V1b-receptor antagonists